KETERLIBATAN ORANG MUDA KATOLIK DALAM PELAYANAN GEREJA DI PEDESAAN : Abtrak, Pendahuluan, Pembahasan, Kesimpulan - Fransisko Amadino Heli; Antonius Denny Firmanto (Jurnal Pelayanan Pastoral, 2023)
Taking part in the ministry of the Catholic Church is a noble and sacred duty because it is directed to Jesus Christ, the owner and head of the Church. Ministry is seen as a spiritual activity that is routinely carried out in the Catholic Christian community, in this case what wants to be discussed in this study is the service of Catholic youth community (OMK) to the church, especially in rural areas. The understanding of the concept of the church began with the formation of a special community, namely the nation of Israel chosen by God and bound by covenant with God. The Church is the fruit of Christ's work which adopts the analogy of the human body to illustrate that there is nothing else, but rather each member has a different function to build and grow the body of Christ. Seeing importance role of young people as the body of Christ who also contributes to building the body of Christ, the church needs to seriously think about youth ministry because youth service is very influential on the growth of the church itself.